Lithium metal battery electrolyte based on flexible molecular conformation regulation and control, preparation method of lithium metal battery electrolyte and lithium metal battery
By regulating the conformation of flexible solvent molecules, the polarity is weakened, and the problems of lithium dendrites growth and electrolyte decomposition during charging and discharging of lithium metal batteries are solved, and efficient lithium metal negative electrode Coulomb efficiency and battery cycle life are achieved. extend.
Patent Information
- Application Number
- CN202411359823.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
AI Technical Summary
The growth of lithium dendrites and the decomposition of electrolyte during the charging and discharging of existing lithium metal batteries leads to degradation of performance and shortening of cycle life, hindering the development of lithium metal batteries.
By introducing diluents that can form hydrogen bonds with flexible solvents, the conformation of flexible solvent molecules is regulated, and their polarity is weak, showing weak solvation properties, broadening the types of solvents of weak solvation electrolytes, and improving anions and lithium Coordination of ions.
The flexible solvation structure adjustment of the lithium metal battery electrolyte is achieved, the growth of lithium dendrites is inhibited, the Coulomb efficiency of the lithium metal negative electrode is improved, the cycle life of the battery is extended, and the production cost is reduced.
Smart Images

Figure CN119447456A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a lithium metal battery electrolyte based on flexible molecular conformation regulation, a preparation method thereof, and a lithium metal battery. Background Art
[0002] Due to the rapid development of mobile electronic devices and electric vehicles, commercial lithium-ion batteries with graphite as anodes are unable to meet the needs of power systems in terms of energy density and service life. Lithium metal anodes have high theoretical specific capacity and ultra-low electrode potential and are considered to be ideal energy storage anodes. However, during the charge and discharge process, the growth of lithium dendrites and the decomposition of the electrolyte greatly reduce the performance of lithium metal batteries, shorten the cycle life of the battery, and seriously hinder the development of lithium metal batteries.
[0003] The electrolyte is a key component for transporting lithium ions, stabilizing the electrochemical window, and regulating the negative electrode interface in lithium metal batteries. Regulating the electrolyte can effectively achieve stable circulation of lithium metal batteries. At present, the schemes for regulating the electrolyte mainly include: high-concentration salt electrolyte, local high-concentration electrolyte and weak solvation electrolyte. High-concentration salt electrolyte uses a large amount of lithium salt to change the solvation structure of the electrolyte, resulting in high viscosity of the electrolyte and poor wettability with the diaphragm. Local high-concentration electrolyte effectively improves the above-mentioned problems of high-concentration salt electrolyte by introducing fluorine-containing inert solvents, but the cost of diluents is expensive and difficult to meet the requirements of the civilian market. Compared with high-concentration salt electrolytes, weak solvation electrolytes can achieve weaker solvent-lithium ion coordination, allowing a large number of anions to enter the solvation shell and participate in coordination. This achieves the goal of constructing a stable solid electrolyte membrane to stabilize the lithium metal negative electrode at a lower lithium salt concentration, but the limited solvent selection is a major problem in constructing a weak solvation electrolyte system. Summary of the invention
[0004] In view of the above problems, in order to expand the types of solvents in weakly solvated electrolytes and improve the compatibility of electrolytes with lithium metal negative electrodes, the present invention provides a lithium metal battery electrolyte based on flexible molecular conformation regulation and a preparation method thereof. The present invention introduces a diluent that can form hydrogen bond interactions with flexible solvent molecules, forms intermolecular hydrogen bonds through the carbon-fluorine bonds in the diluent and the carbon-hydrogen bonds in the flexible solvent molecules, and regulates the conformation of the solvent molecules to weaken the polarity of the flexible molecules, showing weak solvation properties, thereby broadening the types of solvents in weakly solvated electrolytes. In addition, after conformational regulation, the coordination between the weakly solvated molecules and lithium ions is reduced, which effectively improves the coordination between anions and lithium ions, realizes an anion-rich solvation structure, and thus stabilizes the lithium metal negative electrode.
[0005] The technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a lithium metal battery electrolyte based on flexible molecular conformation regulation.
[0007] including a lithium salt, a diluent having a carbon-fluorine bond, and a flexible solvent having a carbon-hydrogen bond;
[0008] The flexible solvent comprises at least one of methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 1,2-bis(trimethylsilyloxy)ethane, 1,3-bis(trimethylsilyloxy)propane, trimethyl phosphate and tris(2,2,2-trifluoroethyl)phosphate;
[0009] The diluent regulates the molecular conformation of the flexible solvent by forming an intermolecular force with the flexible solvent, and the polarity of the flexible solvent becomes weaker under the regulation of the diluent.
[0010] Optionally, the diluent is selected from at least one of fluorobenzene, trifluorotoluene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, hexafluorobenzene, fluorocyclohexylamine and 1-fluoropentane.
[0011] Optionally, the lithium salt is selected from at least one of LiPF6, LiBF4, LiTFSI, LiFSI and LiDFOB.
[0012] Optionally, the molar ratio of the lithium salt, the flexible solvent and the diluent is 1:1-10:1-10.
[0013] Optionally, the molar ratio of the lithium salt, the flexible solvent and the diluent is 1:2-8:2-8.
[0014] Optionally, the molar ratio of the lithium salt, the flexible solvent and the diluent is 1:2-5:3-6.
[0015] Optionally, the lithium salt concentration in the electrolyte is less than 4 mol / L.
[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned electrolyte, comprising: adding a lithium salt into a flexible solvent, adding a diluent after the lithium salt is completely dissolved, and mixing them evenly to obtain a lithium metal battery electrolyte.
[0017] In a third aspect, the present invention provides a lithium metal battery comprising the above-mentioned electrolyte.
[0018] Optionally, the lithium metal battery also includes a negative electrode, a positive electrode and a separator, the negative electrode is a lithium metal negative electrode, the positive electrode is at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and polyacrylonitrile sulfide, and the separator is at least one of a glass fiber separator, a polytetrafluoroethylene separator, a polypropylene separator, a polyethylene separator and a cellulose separator.
[0019] The present invention has at least one of the following beneficial effects:
[0020] 1. The present invention regulates the conformation of flexible solvent molecules by adding a diluent to form an intermolecular force with the flexible solvent, thereby effectively achieving the regulation of the flexible solvation structure of the lithium metal battery electrolyte, weakening the polarity of the flexible solvent and presenting a weak solvation property; and the coordination between the weak solvation molecules and lithium ions after the conformational regulation is reduced, which effectively improves the coordination between anions and lithium ions, can well inhibit the growth of lithium dendrites, and achieve a higher coulombic efficiency of the lithium metal negative electrode.
[0021] 2. The lithium metal battery electrolyte based on flexible molecular conformation regulation of the present invention can expand the selection of solvent molecules for weakly solvating electrolytes. Some solvents can achieve weakly solvating effects by regulating their molecular conformations and can be used to prepare lithium metal battery electrolytes.
[0022] 3. The lithium metal electrolyte of the present invention has a lower lithium salt concentration. The electrolyte has the advantages of low density, low viscosity and high wettability, which greatly improves the ionic conductivity of the lithium metal electrolyte, reduces the production cost of the electrolyte, can be used on a large scale, and has extremely high commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the nuclear magnetic resonance spectrum of the electrolyte in Example 1 of the present invention;
[0024] Figure 2 is a SEM picture of lithium metal deposited in the electrolyte in Example 1 of the present invention;
[0025] Figure 3 is a SEM cross-sectional image of lithium metal deposited in the electrolyte in Example 1 of the present invention;
[0026] Figure 4 is a time-voltage curve of the deposition and stripping of lithium metal in the electrolyte in Example 1 of the present invention;
[0027] Figure 5 is a long cycle data diagram of lithium metal in an electrolyte in Example 1 of the present invention;
[0028] Figure 6 is a graph of the cycle capacity of lithium / polyacrylonitrile sulfide in an electrolyte in Example 1 of the present invention;
[0029] Figure 7 is a time-voltage curve of deposition and stripping of lithium metal in an electrolyte in Example 2 of the present invention;
[0030] Figure 8 is a long cycle data diagram of lithium metal in an electrolyte in Example 2 of the present invention;
[0031] Fig. 9is a time-voltage curve of deposition and stripping of lithium metal in an electrolyte in Example 3 of the present invention;
[0032] Fig.10 is a long cycle data diagram of lithium metal in an electrolyte in Example 3 of the present invention;
[0033] Fig.11 is a time-voltage curve of the deposition and stripping of lithium metal in the electrolyte in Comparative Example 1;
[0034] Fig.12 This is a time-voltage curve of the deposition and stripping of lithium metal in the electrolyte in Comparative Example 4. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] An embodiment of the present invention provides a lithium metal battery electrolyte based on flexible molecular conformation regulation.
[0037] including a lithium salt, a diluent having a carbon-fluorine bond, and a flexible solvent having a carbon-hydrogen bond;
[0038] The flexible solvent comprises at least one of methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 1,2-bis(trimethylsilyloxy)ethane, 1,3-bis(trimethylsilyloxy)propane, trimethyl phosphate and tris(2,2,2-trifluoroethyl)phosphate.
[0039] The diluent regulates the molecular conformation of the flexible solvent by forming an intermolecular force with the flexible solvent, and the polarity of the flexible solvent becomes weaker under the regulation of the diluent.
[0040] The "flexibility" of a molecule refers to the internal rotation freedom of the molecule. The internal rotation of the CC bond within the molecule will affect the properties of the molecule.
[0041] The "flexible solvent" in the present invention refers to a type of solvent whose molecules have internal rotational freedom.
[0042] The present invention introduces a diluent that can form intermolecular interactions with flexible solvent molecules, forms intermolecular hydrogen bonds through carbon-fluorine bonds in the diluent and carbon-hydrogen bonds in the flexible solvent molecules, and regulates the conformation of the solvent molecules to weaken the polarity of the flexible molecules, presenting weak solvation properties, and broadening the types of solvents for weak solvation electrolytes. In addition, after conformational regulation, the coordination between the weak solvation molecules and lithium ions is reduced, which effectively improves the coordination between anions and lithium ions, realizes anion-rich solvation structure, and thus stabilizes the lithium metal negative electrode.
[0043] The diluent regulates the molecular conformation of the flexible solvent in the form of intermolecular hydrogen bonds formed by carbon-fluorine bonds and carbon-hydrogen bonds in the flexible solvent, and the polarity of the flexible solvent becomes weaker under the regulation of the diluent.
[0044] In some embodiments, the diluent is selected from at least one of fluorobenzene, trifluorotoluene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, hexafluorobenzene, fluorocyclohexylamine and 1-fluoropentane.
[0045] In some embodiments, the lithium salt is selected from at least one of LiPF6, LiBF4, LiTFSI, LiFSI and LiDFOB.
[0046] The applicant has found through research that the molar ratio of lithium salt, flexible solvent and diluent will affect the performance of the electrolyte, especially the molar ratio of the flexible solvent and the diluent. This may be because the molar ratio of the flexible solvent and the diluent will affect the regulation effect of the diluent on the flexible solvent. Therefore, in some embodiments, the molar ratio of the lithium salt, the flexible solvent and the diluent is 1:1-10:1-10. Preferably, the molar ratio of the lithium salt, the flexible solvent and the diluent is 1:2-8:2-8. More preferably, the molar ratio of the lithium salt, the flexible solvent and the diluent is 1:2-5:3-6. After research, it was found that when the molar ratio of the lithium salt, the flexible solvent and the diluent is 1:2-5:3-6, the coulombic efficiency of the lithium copper battery assembled using this type of electrolyte can reach more than 99%. Specifically, it can be 1:2:2, 1:2:4, 1:2:5, 1:2:6, 1:3:4, 1:3:5, 1:3:6 or 1:4:6, etc., especially when it is 1:3:6, the coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte can be as high as 99.5%.
[0047] In some embodiments, the lithium salt concentration in the electrolyte is less than 4 mol / L. Preferably, the lithium salt concentration in the electrolyte is less than 3 mol / L. More preferably, the lithium salt concentration in the electrolyte is less than 2 mol / L.
[0048] Another embodiment of the present invention provides a method for preparing the above-mentioned electrolyte, comprising: adding a lithium salt into a flexible solvent, adding a diluent after the lithium salt is completely dissolved, and mixing them evenly to obtain a lithium metal battery electrolyte.
[0049] This method can form intermolecular interactions between the diluent and the flexible solvent molecules to regulate the conformation of the flexible solvent molecules, weaken the polarity of the flexible solvent molecules, and exhibit weak solvation properties.
[0050] Another embodiment of the present invention provides a lithium metal battery, comprising the above-mentioned electrolyte.
[0051] The lithium metal battery prepared by the present invention has an electrolyte that exhibits a weak solvation property, thereby achieving a stable cycle of the lithium metal battery; moreover, the coordination between the weak solvation molecules and lithium ions is reduced, which effectively improves the coordination between the anions and lithium ions, achieving an anion-rich solvation structure, thereby stabilizing the lithium metal negative electrode.
[0052] In some embodiments, the lithium metal battery also includes a negative electrode, a positive electrode and a separator, the negative electrode is a lithium metal negative electrode, the positive electrode is at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and polyacrylonitrile sulfide, and the separator is at least one of a glass fiber separator, a polytetrafluoroethylene separator, a polypropylene separator, a polyethylene separator and a cellulose separator.
[0053] The applicant has found through research that the molecular structure of the solvent is closely related to the change in its properties. Among them, molecular conformation refers to the special spatial arrangement of carbon atoms and hydrogen atoms in the molecule, which rotate around the carbon-carbon single bond and transform into each other. Even for molecules with smaller volumes, the changes in their conformation are huge. In electrolyte optimization, by regulating the conformation of solvent molecules, the properties of solvent molecules can be changed, so that the molecules exhibit weak solvation characteristics. This regulation can effectively expand the types of solvents in weakly solvating electrolytes.
[0054] Therefore, the present invention introduces a diluent that can form hydrogen bond interactions with flexible solvent molecules. By forming intermolecular hydrogen bonds between the carbon-fluorine bonds in the diluent and the carbon-hydrogen bonds in the flexible solvent molecules, the conformation of the solvent molecules is regulated to weaken the polarity of the flexible molecules, exhibiting weak solvation properties, thereby broadening the types of solvents for weak solvation electrolytes.
[0055] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0056] It should be noted that:
[0057] 1. Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0058] 2. The performance of the lithium-ion battery electrolytes prepared in the following examples was tested in the following manner:
[0059] The lithium copper battery is assembled in the order of lithium sheet / diaphragm / copper foil, with a thickness of 100 microns and a diameter of 12 mm as the negative electrode and a thickness of 10 microns and a diameter of 19 mm as the positive electrode. The charge and discharge cycle of the lithium metal battery is tested by assembling the lithium sheet / diaphragm / polyacrylonitrile sulfide battery. All battery tests are conducted on the Xinwei charge and discharge test system, and the corresponding data are obtained.
[0060] Embodiment 1:
[0061] At room temperature and pressure, firstly, lithium bis(fluorosulfonyl)imide is added to 2,5-dimethyltetrahydrofuran, and stirred with a magnetic stirrer, and after the lithium salt is completely dissolved, a diluent, trifluorotoluene, is added, that is, lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran, and trifluorotoluene are prepared into a uniform solution in a molar ratio of 1:3:4 to obtain a lithium metal battery electrolyte;
[0062] The prepared electrolyte was used to assemble a lithium copper battery at 0.5 mA cm -2 The current density was 1mAcm and the charge and discharge time was 2h for long cycle test. -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal was charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface was passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The lithium metal battery was assembled with polysulfide acrylonitrile as the positive electrode, polypropylene as the separator, and lithium metal as the negative electrode. The charge and discharge range was set at 1-3V for cycle testing.
[0063] test:
[0064] (1) The prepared electrolyte was tested using nuclear magnetic resonance spectroscopy. Compared with 2,5-dimethyltetrahydrofuran itself ( Figure 1 2,5-THF in) and a mixed system of lithium bis(fluorosulfonyl)imide and 2,5-dimethyltetrahydrofuran ( Figure 1 LiFSI 2,5-THF) contains lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran and trifluorotoluene ( Figure 1 In the above electrolyte of LiFSI 2,5-THF+BTF), a significant decrease in the nuclear magnetic coupling constant was found, as shown in the following figure. Figure 1 As shown, it is indicated that the electrolyte of the present invention can effectively regulate the conformation of solvent molecules.
[0065] (2) The lithium metal battery electrolyte and lithium sheet, separator and copper foil are used to assemble a lithium copper half-cell at 0.5 mA cm -2 The lithium metal was deposited at a current density of 1000 nm for 1 h. After the deposition was completed, the lithium-copper battery was disassembled, and the copper foil on which the lithium metal was deposited was taken out. The microscopic deposition morphology was observed under a scanning electron microscope. Figure 2 As shown, the deposition interface morphology is obtained as Figure 3 shown.
[0066] Depend on Figure 2 It can be seen that after using the conformation-regulated lithium metal battery electrolyte, the surface of lithium metal deposited on the copper foil is smooth and uniform; Figure 3 Scanning electron microscope images show that the lithium metal deposited using the electrolyte is dense and uniform without dendrite growth, indicating that the electrolyte of the present invention can effectively stabilize the lithium metal negative electrode.
[0067] (3) The lithium copper battery assembled using the above electrolyte was -2 The coulombic efficiency was tested at a current density of Figure 4 shown.
[0068] Depend on Figure 4 It can be seen that the coulombic efficiency of the lithium-copper battery assembled using the lithium metal battery electrolyte regulated by this conformation reaches 99.4%.
[0069] (4) The above electrolyte was used to assemble a lithium copper battery at 0.5 mA cm -2 At a current density of , the charge and discharge time is 2h for long cycle test. Figure 5 As shown, the lithium metal negative electrode can stably cycle 1000 times in the electrolyte, indicating that the electrolyte can stabilize the lithium metal negative electrode well.
[0070] (5) The above electrolyte was used to assemble a lithium metal-polyacrylonitrile sulfide full battery with lithium metal, a separator, and polyacrylonitrile sulfide. The battery was 250 mAh g -1 The charge and discharge cycles are carried out at a current density of Figure 6 As shown, the full battery can stably cycle 700 cycles in this electrolyte with a capacity retention rate of 79%.
[0071] Embodiment 2:
[0072] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to 2,5-dimethyltetrahydrofuran, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, the diluent 1,2-difluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran, and 1,2-difluorobenzene are prepared into a uniform solution in a molar ratio of 1:2:4 to obtain a lithium metal battery electrolyte:
[0073] (1) Assemble a lithium copper battery using the electrolyte prepared above at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated.
[0074] Depend on Figure 7 As shown, the coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reaches 99.4%.
[0075] (2) The above electrolyte was used to assemble a lithium copper battery at 0.5 mA cm -2 At a current density of , the charge and discharge time is 2h for long cycle test. Figure 8 As shown, the lithium metal negative electrode can stably cycle 200 times in the electrolyte, indicating that the electrolyte is well compatible with the lithium metal negative electrode.
[0076] Embodiment 3:
[0077] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to 2,5-dimethyltetrahydrofuran, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, a diluent 1,4-difluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran, and 1,4-difluorobenzene are prepared into a uniform solution in a molar ratio of 1:3:6 to obtain a lithium metal battery electrolyte:
[0078] (1) Using the prepared electrolyte, a lithium copper battery was assembled at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal was charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface was passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated.
[0079] Depend on Fig. 9 As shown, the coulombic efficiency of lithium-copper batteries assembled using this type of electrolyte reaches 99.5%.
[0080] (2) The above electrolyte was used to assemble a lithium copper battery at 0.5 mA cm -2 At a current density of , the charge and discharge time is 2h for long cycle test. Fig.10 As shown, the lithium metal negative electrode can stably cycle 200 times in the electrolyte, indicating that the electrolyte is well compatible with the lithium metal negative electrode.
[0081] Embodiment 4:
[0082] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to methyltetrahydrofuran, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, trifluorotoluene is added as a diluent, that is, lithium bis(fluorosulfonyl)imide, methyltetrahydrofuran, and trifluorotoluene are prepared in a molar ratio of 1:2:5 to form a uniform solution, thereby obtaining a lithium metal battery electrolyte:
[0083] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reached 99.0%.
[0084] Embodiment 5:
[0085] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to methyltetrahydrofuran, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, a diluent 1,4-difluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, methyltetrahydrofuran, and 1,4-difluorobenzene are prepared in a molar ratio of 1:4:5 to form a uniform solution, and a lithium metal battery electrolyte is obtained:
[0086] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal was charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface was passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and at 1.0 mA cm -2 At a current density of 1 mAh cm -2The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reached 99.2%.
[0087] Embodiment 6:
[0088] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to methyltetrahydrofuran, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, the diluent 1,2,3-trifluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, methyltetrahydrofuran, and 1,2,3-trifluorobenzene are prepared in a molar ratio of 1:4:6 to form a uniform solution to obtain a lithium metal battery electrolyte:
[0089] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reached 99.3%.
[0090] Embodiment 7:
[0091] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to 1,2-bis(trimethylsilyl)ethane, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, a diluent 1,2-difluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, 1,2-bis(trimethylsilyl)ethane, and 1,2-difluorobenzene are prepared into a uniform solution in a molar ratio of 1:2:6 to obtain a lithium metal battery electrolyte:
[0092] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm-2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reached 99.2%.
[0093] Embodiment 8:
[0094] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to 1,2-bis(trimethylsilyl)ethane, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, diluent hexafluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, 1,2-bis(trimethylsilyl)ethane, and hexafluorobenzene are prepared into a uniform solution in a molar ratio of 1:3:3 to obtain a lithium metal battery electrolyte:
[0095] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reached 99.2%.
[0096] Embodiment 9:
[0097] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to 1,3-bis(trimethylsilyl)propane, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, diluent hexafluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, 1,3-bis(trimethylsilyl)propane, and hexafluorobenzene are mixed in a molar ratio of 1:5:5 to form a uniform solution, and a lithium metal battery electrolyte is obtained:
[0098] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reached 99.0%.
[0099] Embodiment 10:
[0100] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to 1,3-bis(trimethylsilyl)propane, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, a diluent, fluorocyclohexylamine, is added. That is, lithium bis(fluorosulfonyl)imide, 1,3-bis(trimethylsilyl)propane, and fluorocyclohexylamine are mixed in a molar ratio of 1:3:5 to form a uniform solution to obtain a lithium metal battery electrolyte:
[0101] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface, and the coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reached 99.4%.
[0102] Comparative Example 1:
[0103] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to tetrahydrofuran, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, trifluorotoluene is added as a diluent, that is, lithium bis(fluorosulfonyl)imide, tetrahydrofuran, and trifluorotoluene are prepared in a molar ratio of 1:3:4 to form a uniform solution, thereby obtaining a lithium metal battery electrolyte:
[0104] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface. The coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The lithium-copper battery assembled using this type of electrolyte cannot be cycled normally. The electrolyte and lithium metal are not well compatible, such as Fig.11 shown.
[0105] Comparative Example 2:
[0106] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to tetrahydrofuran and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, diluent fluorobenzene is added, that is, lithium bis(fluorosulfonyl)imide, tetrahydrofuran, and fluorobenzene are prepared in a molar ratio of 1:3:5 to form a uniform solution to obtain a lithium metal battery electrolyte.
[0107] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface. The coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The lithium-copper battery assembled using this type of electrolyte cannot be cycled normally, and the electrolyte is not well compatible with lithium metal.
[0108] Comparative Example 3:
[0109] At room temperature and pressure, lithium bis(fluorosulfonyl)imide is first added to tetrahydrofuran, and stirred using a magnetic stirrer. After the lithium salt is completely dissolved, a diluent, fluorocyclohexylamine, is added, that is, lithium bis(fluorosulfonyl)imide, tetrahydrofuran, and fluorocyclohexylamine are prepared in a molar ratio of 1:3:4 to form a uniform solution to obtain a lithium metal battery electrolyte.
[0110] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm-2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface. The coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte was 92.0%.
[0111] Comparative Example 4
[0112] At room temperature and pressure, firstly, lithium bis(fluorosulfonyl)imide is added to 2,5-dimethyltetrahydrofuran, and stirred with a magnetic stirrer, and after the lithium salt is completely dissolved, diluent toluene is added, that is, lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran, and toluene are prepared into a uniform solution in a molar ratio of 1:3:4 to obtain a lithium metal battery electrolyte;
[0113] The prepared electrolyte was used to assemble a lithium copper battery at 1 mA cm -2 The current density was discharged for 10 h, and 10 mAh cm was deposited on the copper foil. -2 The lithium metal is charged at a cut-off voltage of 1 V to completely strip off the deposited lithium metal and ensure that the copper foil surface is passivated. -2 The current density was discharged for 10 h and then 10 mAh cm was deposited. -2 Li metal was deposited on the copper foil surface and then charged at 1.0 mA cm -2 At a current density of 1 mAh cm -2 The capacity of the battery was cycled 10 times, and finally the voltage was set to 1V to completely peel off the lithium metal from the copper foil surface. The coulombic efficiency of the lithium metal negative electrode in the electrolyte was calculated. The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte is 96.0%. Fig.12 shown.
[0114] Comparative Example 5
[0115] The difference from Example 1 is that lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran, and trifluorotoluene are prepared into a uniform solution in a molar ratio of 1:2:15;
[0116] The rest is the same as Example 1.
[0117] The coulombic efficiency of lithium-copper batteries assembled using this type of electrolyte reaches 96.5%.
[0118] Comparative Example 6
[0119] The difference from Example 1 is that lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran, and trifluorotoluene are prepared into a uniform solution in a molar ratio of 1:15:2;
[0120] The rest is the same as Example 1.
[0121] The coulombic efficiency of lithium-copper batteries assembled using this type of electrolyte reaches 95.2%.
[0122] Comparative Example 7
[0123] The difference from Example 1 is that lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran and trifluorotoluene are prepared into a uniform solution in a molar ratio of 3:3:4;
[0124] The rest is the same as Example 1.
[0125] The coulombic efficiency of lithium-copper batteries assembled using this type of electrolyte reaches 97.0%.
[0126] Comparative Example 8
[0127] The difference from Example 1 is that lithium bis(fluorosulfonyl)imide, 2,5-dimethyltetrahydrofuran and trifluorotoluene are prepared into a uniform solution in a molar ratio of 0.5:3:4;
[0128] The rest is the same as Example 1.
[0129] The coulombic efficiency of the lithium-copper battery assembled using this type of electrolyte reaches 93.0%.
[0130] The coulombic efficiency of the lithium-copper battery assembled with the electrolyte prepared in Example 1 (experimental group) and Comparative Examples 1 to 8 was compared. Among them, Comparative Examples 1 to 3 changed the type of solvent. Tetrahydrofuran was used in Comparative Examples 1 to 3, and trifluorotoluene, fluorobenzene, and fluorocyclohexylamine were used as diluents, respectively. However, the lithium-copper battery assembled with the electrolyte prepared in Comparative Examples 1 to 2 could not circulate normally, and the electrolyte was not well compatible with lithium metal. The coulombic efficiency of the lithium-copper battery assembled with the electrolyte in Comparative Example 3 was reduced. This is because tetrahydrofuran is a rigid molecule and cannot be hydrogen bonded. The interaction changes its molecular structure, so after the diluent is added, the tetrahydrofuran solvent molecules will preferentially participate in the coordination with the lithium ions and decompose on the electrode surface, resulting in poor coulombic efficiency of the lithium-copper battery or even inability to cycle; Comparative Example 4 changes the type of diluent and adopts toluene, a diluent that does not contain carbon-fluorine bonds. Since toluene cannot form intermolecular hydrogen bonds with the carbon-hydrogen bonds in the solvent to regulate the molecular conformation of the solvent, the polarity of the flexible solvent will not weaken, and the coulombic efficiency of the lithium-copper battery assembled by the prepared electrolyte is only 96.0%, which is significantly lower than that of Example 1. In comparative example 5, too much diluent is added, resulting in a side reaction between the diluent and lithium metal; in comparative example 6, too much flexible solvent is added, resulting in a large amount of solvent decomposition at the lithium metal interface; in comparative example 7, too much lithium salt is added, resulting in the inability to completely dissolve the lithium salt and the problem of a solid-liquid mixed solution of the electrolyte; in comparative example 8, too little lithium salt is added, resulting in a reaction between the diluent and lithium metal, and at the same time, the solvent decomposes at the lithium metal interface; thus, the coulombic efficiency of the lithium-copper battery assembled from the electrolytes prepared in comparative examples 5 to 8 is only 93.0 to 97.0%, which is significantly lower than that in Example 1, which shows that the electrolyte prepared by the present invention can effectively improve the cycle stability of the lithium metal negative electrode.
[0131] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A lithium metal battery electrolyte based on flexible molecular conformation regulation, characterized in that: including a lithium salt, a diluent having a carbon-fluorine bond, and a flexible solvent having a carbon-hydrogen bond; The flexible solvent comprises at least one of methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 1,2-bis(trimethylsilyloxy)ethane, 1,3-bis(trimethylsilyloxy)propane, trimethyl phosphate and tris(2,2,2-trifluoroethyl)phosphate; The diluent regulates the molecular conformation of the solvent by forming an intermolecular force with the flexible solvent, and the polarity of the flexible solvent becomes weaker under the regulation of the diluent.
2. The electrolyte according to claim 1, characterized in that The diluent is selected from at least one of fluorobenzene, trifluorotoluene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, hexafluorobenzene, fluorocyclohexylamine and 1-fluoropentane.
3. The electrolyte according to claim 1, characterized in that The lithium salt is selected from at least one of LiPF6, LiBF4, LiTFSI, LiFSI and LiDFOB.
4. The electrolyte according to claim 1, characterized in that The molar ratio of the lithium salt, the flexible solvent and the diluent is 1:1-10:1-10.
5. The electrolyte according to claim 1, characterized in that The molar ratio of the lithium salt, the flexible solvent and the diluent is 1:2-8:2-8.
6. The electrolyte according to claim 1, characterized in that The molar ratio of the lithium salt, the flexible solvent and the diluent is 1:2-5:3-6.
7. The electrolyte according to claim 1, characterized in that The lithium salt concentration in the electrolyte is less than 4 mol / L.
8. A method for preparing an electrolyte according to any one of claims 1 to 7, characterized in that: include: Add lithium salt into a flexible solvent, add a diluent after the lithium salt is completely dissolved, mix well, and obtain a lithium metal battery electrolyte.
9. A lithium metal battery, characterized in that: The invention comprises the electrolyte according to any one of claims 1 to 7 or the electrolyte obtained by the preparation method according to claim 8.
10. The lithium metal battery according to claim 9, characterized in that The lithium metal battery also includes a negative electrode, a positive electrode and a separator, the negative electrode is a lithium metal negative electrode, the positive electrode is at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and polyacrylonitrile sulfide, and the separator is at least one of a glass fiber separator, a polytetrafluoroethylene separator, a polypropylene separator, a polyethylene separator and a cellulose separator.